BRANDING MADRASAH MELALUI MEDIA SOSIAL SEBAGAI STRATEGI PUBLIKASI DAN PENINGKATAN CITRA MADRASH TSANAWIYAH DIPODRONO - Muhamad Rio Wijaya; Faiq Yunianto; Novi Andriani; Jesica Elvira Setyawan; Saryadi; Nayla Khumaida (Institut Agama Islam Syubbanul Wathon Magelang, 2025)
This community service program aims to enhance the image and publication of MTs Dipodrono Sukomakmur through social media branding strategies. The activities were conducted in August 2025 in Sukomakmur Village, Magelang Regency, employing the Asset-Based Community Development (ABCD) method with the 5D framework (Discovery, Dream, Define, Design, Destiny). The main focus was leveraging internal school assets—such as student achievements, religious activities, and infrastructure—as digital content materials. The results demonstrated the effectiveness of this approach, with quantitative indicators showing a 150% increase in average engagement (likes and reach) and a 20% growth in Instagram followers within one month. Operationally, the program successfully established a social media management team consisting of administrative staff (TU), whose content management roles are integrated into their institutional administrative duties. While further technical assistance is required, the program has established a foundation for branding sustainability and strengthened the school's image as an high-achieving, innovative, and religious institution in the digital era.